2004
DOI: 10.4028/www.scientific.net/msf.443-444.159
|View full text |Cite
|
Sign up to set email alerts
|

Performance Stability of Microfocusing Source and Multilayer Optics Based X-Ray Diffraction System

Abstract: X-ray diffraction systems based on a microfocusing X-ray source and multilayer side-by-side optics are suitable for X-ray diffraction studies in a variety of fields, such as protein crystallography, due to their compactness and low cost in maintenance. However, new problems can occur, such as intensity instability induced by source position drifting. Various investigations for the reasons and the consequences of the instability are presented in this paper. Feasible solutions and suggestions are given to obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…Microfocusing compact X-ray sources have been used more widely in recent years [86], and its applications are connected to the X-ray focusing optics. The benefits of these compact X-ray sources include low power consumption, usually of the order of a few to a few tens of watts; small source sizes, of the order of tens of micrometers or smaller; and compact sizes.…”
Section: Cw X-ray Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Microfocusing compact X-ray sources have been used more widely in recent years [86], and its applications are connected to the X-ray focusing optics. The benefits of these compact X-ray sources include low power consumption, usually of the order of a few to a few tens of watts; small source sizes, of the order of tens of micrometers or smaller; and compact sizes.…”
Section: Cw X-ray Sourcesmentioning
confidence: 99%
“…The small source size is important because it allows the use of high-resolution X-ray focusing optics to refocus the X-rays emitted from the source to another place at a distance so that other measurements can be easily performed. Kim et al demonstrated how this is achieved with a multiple layer X-ray focusing optics [86]. Although this source has mainly been used for X-ray diffraction, it is foreseeable that it can also be used for X-ray spectroscopy.…”
Section: Cw X-ray Sourcesmentioning
confidence: 99%